CREATION AND RESEARCH OF THE NATIONAL STANDARD OF CAPACITANCE - T. A. Kolomiets; E. A. Kazakova; T. G. Sosnovskaya (Приборы и методы измерений, 2015)
In 2008–2010 the Belorussian State Institute of Metrology established the national electric capacitance standard. The basic steps for creating a national standard are presented in this manuscript. Represented by the composition of the standard, its metrological characteristics, as well as research results.